Italian healthcare professionals' attitude and barriers to mandatory reporting of elder abuse: An exploratory study. (April 2019) - Mazzotti, Maria Carla; Scarcella, Elena; D'Antone, Elisa; Fersini, Federica; Salsi, Giancarlo; Ingravallo, Francesca; Amadasi, Alberto; Pelotti, Susi
Abstract: Introduction: Elder abuse in recent times has reached a remarkable international importance. This complex phenomenon is still little understood and studied in Italy. The aim of this study was to explore Italian healthcare professionals' attitude and barriers toward elder abuse, with a glimpse on the current scenario and evidences to develop an action plan. Materials and methods: 42 healthcare professionals filled a questionnaire with 13 open-ended questions, analyzed with a qualitative content analysis. Data were grouped under the following 4 core-themes: description of elder abuse, abuse detection and perception, barriers to reporting, and professional orientation and approach; then they were analyzed to find their central component and discussed jointly. Results: The respondents described physical (64%) and psychological (50%) abuse and neglect (50%) as the three main characteristics of elder abuse; the 59% of them reported at least one experience in detecting or suspecting elder abuse. The 76% of participants believed the report has to be submitted to the Judicial Authority only in presence of compelling evidences. Furthermore, the 73% of the sample perceived that healthcare professionals are the main figures who have to cope with elder abuse, however they did not feel as their exclusive role the assessment of the patients' potential abuse. Conclusion: Knowledge about elder abuse was limited to physical/psychological issues and, moreover, the legal obligation to report was only poorly known. Imperative is the creation of specific education and training courses, in addition to the need for a multidisciplinary and empathetic approach. Highlights: Elder abuse is a major public health concern which poses many challenges to prevention and treatment. It is one of the most neglected types of violence and only a very small number of elder maltreatments are reported. The role of healthcare professionals in the identification and assessment of risk factors of elder abuse is crucial. The results of this study may provide further support in order to properly address elder abuse in Italy.